1. 1)K2S + 2HCl = 2KCl + H2S
2K(+) + S(2-) + 2H(+) + 2Cl(-) = 2K(+) + 2Cl(-) + H2S
2H(+) + S(2-) = H2S
2)K2S + NaNO3 - реакция не идёт
3)K2SO4 + Pb(NO3)2 = PbSO4 + 2KNO3
2K(+) + SO4(2-) + Pb(2+) + 2NO3(-) = PbSO4 + 2K(+) + 2NO3(-)
Pb(2+) + SO4(2-) = PbSO4
2. 1)Fe(3+) + 3OH(-) = Fe(OH)3
Fe(3+) + 3NO3(-) + Al(3+) + 3OH(-) = Fe(OH)3 + Al(3+) + 3NO3(-)
Fe(NO3)3 + Al(OH)3 = Fe(OH)3 + Al(NO3)3
2)2H(+) + S(2-) = H2S
2H(+) + 2Cl(-) + 2K(+) + S(2-) = 2K(+) + 2Cl(-) + H2S
2HCl + K2S = 2KCl + H2S
3)3Ca(2+) + 2PO4(3-) = Ca3(PO4)2
3Ca(2+) + 6Cl(-) + 6K(+) + 2PO4(3-) = Ca3(PO4)2 + 6K(+) + 6Cl(-)
3CaCl2 + 2K3PO4 = Ca3(PO4)2 + 6KCl